Characterization Of Indium Based Low Temperature Solder Alloy And The Effect On Surface Finish - Mhd Noor, Ervina Efzan (2013)

(untitled)
The increased use of electronic devices has increased the usage of solder connections. Lead, the prime solder hitherto used, is hazardous to human health and the environment. Thus, replacing Sn-37Pb with a lead-free solder is one of the most important issues in the electronics industry. As such, the characteristics of In-Bi-Sn and In-Bi-Zn compared with that of the Sn-Ag-Cu solder alloy were studied. In the differential scanning calometry analysis, In-Bi-Sn and In-Bi-Zn system alloys presented a low melting temperature of 61.3 °C and 72.3 °C, respectively. Surface tension and contact angle of In-Bi-Sn and In-Bi-Zn lead-free solder alloys were measured on Cu substrate and different surface finishes at 100, 120 and 140 °C reflow. Sessile drop measurements showed that the contact angle depended on the reflow temperature. The contact angle gradually decreased from 30.76° to 17.25° as reflow temperature increased from 100 to 140 °C and for In-Bi-Sn and In-Bi-Zn solder alloy on Cu substrate, ranged from 58° to 7° after wetting on Ni/Cu substrate at the same reflow temperature range (100 to 140°C). Energy-dispersive X-ray analysis found two layers of intermetallic compound in the In-Bi-Sn solder alloy: Cu6Sn5 and Cu11In9 (scallop shaped) and Cu11In9 (brightly coloured) with Cu and Sn/Cu substrate. The IMC between the In-Bi-Zn solder alloy could be observed: Cu5Zn8 (continuous planar) and Cu11In9, a minor IMC layer with Cu and Sn/Cu substrate. However, only one type of IMC was formed between both solders (In-Bi- Sn and In-Bi-Zn) and Ni/Cu substrate, which was InNi2. As the reflow temperature increased, the shear strength of the In-Bi-Sn and In-Bi-Zn solder alloys on Cu, Ni/Cu and Sn/Cu joints improved due to reduced contact angle and larger spreading area